Respon Rumput Gajah (Pennisetum purpureum) Terhadap Pemberian Pupuk Majemuk - Maria Erviana Kusuma (Fakultas Peternakan Universitas Kristen Palangka Raya, 2014)
The aim of this research were to know the effect of some kind compound fertilizer that giving the best result of vegetative growth and production of elephant grass (Pennisetum purpureum). This research was designed by using Completely Random Design with the kind of compound fertilizer as single factor experiment, m0 = control (without compound fertilizer), m1 = compound fertilizer (16:16:16), m2 = compound fertilizer (15:15:6) and m3 = compound fertilizer (20:10:10). The result showed that the applications compound fertilizer giving the influences to the vegetative growth and production of elephant grass (Pennisetum purpureum). The vegetative growth and average production show the same tendency where the compound fertilizer (16:16:16) do not different from the compound fertilizer (15:15:6), but the compound fertilizer (16:16;16) giving the highest than the other compound fertilizer and control.